Regulation of STA1 gene expression by MAT during the life cycle of Saccharomyces cerevisiae. - Dranginis, A M (1989)
STA1 encodes a secreted glucoamylase of the yeast Saccharomyces cerevisiae var. diastaticus. Glucoamylase secretion is controlled by the mating type locus MAT; a and alpha haploid yeast cells secrete high levels of the enzyme, but a/alpha diploid cells produce undetectable amounts. It has been suggested that STA1 is regulated by MATa2 (I. Yamashita, Y. Takano, and S. Fukui, J. Bacteriol. 164:769-773, 1985), which is a MAT transcript of previously unknown function. In contrast, this work shows that deletion of the entire MATa2 gene had no effect on STA1 regulation but that deletion of MATa1 sequences completely abolished mating-type control. In all cases, glucoamylase activity levels reflected STA1 mRNA levels. It appears that STA1 is a haploid-specific gene that is regulated by MATa1 and a product of the MAT alpha locus and that this regulation occurs at the level of RNA accumulation. STA1 expression was also shown to be glucose repressible. STA1 mRNA was induced in diploids during sporulation along with SGA, a closely linked gene that encodes an intracellular sporulation-specific glucoamylase of S. cerevisiae. A diploid strain with a MATa1 deletion showed normal induction of STA1 in sporulation medium, but SGA expression was abolished. Therefore, these two homologous and closely linked glucoamylase genes are induced by different mechanisms during sporulation. STA1 induction may be a response to the starvation conditions necessary for sporulation, while SGA induction is governed by the pathway by which MAT regulates sporulation. The strain containing a complete deletion of MATa2 grew, mated, and sporulated normally.